Approach to the choice of modernization directions for the system of geodynamic monitoring in cases of using components intensity uncertainty - O.R. Kuzichkin; V.T. Eremenko; I.V. Loginov; A.V. Eremenko; S. V. Eremenko; A.V. Grecheneva; G.S. Vasilyev (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
The problem of the optimum choice of the modernization directions for geodynamic monitoring systems, which is solved in the conditions of changing the parameters of natural-technical systems (NTS) is considered in the work. The solution of the task is creating a list of the components modernization directions and validate ranking the most effective of them. As criterion of modernization the value of decrease in resource intensity of subsystem application is using. The task is considering the uncertainty of quantity of the arriving tasks. Within the suggested method, it is offered to determine the effect of resource by each modernization direction. The functional dependences on its increase depending on an expense of resources of modernization. The decision is reached by minimization of total cost of modernization resources for the system in the conditions of change using components intensity at change of external conditions.